The Science of Reading : a Handbook. - Snowling, Margaret J. (Blackwell handbooks of developmental psychology., 2007)
The Science of Reading: A Handbook brings together state-of-the-art reviews of reading research from leading names in the field, to create a highly authoritative, multidisciplinary overview of contemporary knowledge about reading and related skills.:.; Provides comprehensive coverage of the subject, including theoretical approaches, reading processes, stage models of reading, cross-linguistic studies of reading, reading difficulties, the biology of reading, and reading instruction.; Divided into seven sections:Word Recognition Processes in Reading; Learning to Read and Spell; Reading Comprehen.